Molecular Study to Detect Some Virulence Factors in Vaginal Pathogenic Bacteria - Huda J. Rashed; Jasim H. Makhrmash; Abeer H. Maslat (Scientific Trends, 2023)
Background Bacterial vaginosis (BV) is a vaginal microbiome dysbiosis that is reported to be the most common gynecological condition in women of reproductive age (1). Methods: A total 120 swab samples were collected from patients with age 18 –50 years, during the period from 7th November, 2021 to 28th February, 2022 that admitted to Al-Zahra Teaching Hospital, Al Kut Hospital, , and private clinics in Wasit province. Bacteria were isolated and identified using biochemical test, then PCR was used in order to analysis he 16S rRNA gene in bacterial isolates and virulence genes using specific primers. Results: The results of bacterial cultures indicated the presence of four bacterial isolates included E.coli, K. pneumonia, E. faecalis and S. haemolyticus, PCR product analysis of the 16S rRNA gene in bacterial isolates showed that all bacteria 100% were positive for 16S rRNA gene. PCR analysis of virulence factor a total of E. coli, K. pneumoniae, E. faecalis, and S. haemolyticus isolates were confirmed by molecular technique using 16S rRNA. These concentrations and purity were identified by the Nanodrop technique. The concentration was between 50 and 360 ng/l, and the purity was 1.8 to 2.0. In the current study, thirteen virulence genes (fimD, rfbE, mrkD, ecpA, esp, gelE, mecA, icaD, icaA) were utilized and detected by polymerase chain reaction. Escherichia coli possessed 100% and fimD 42%, respectively. On the other hand, K. pneumoniae isolates expressed positive results for 90% of the ecpA and gene tests. However, possess revealed 90% for mrkD and 90% for genes. 83% of E. faecalis isolates tested positive for the esp gene and 83% tested positive for the gelE gene. Finally, S. haemolyticus isolates 100% and 100% for the mecA gene. Conclusion: There was a high prevalence of virulence genes among bacterial isolates included in the current study especially, in E.coli 100%, and E. faecalis, while S. haemolyticus icaD, icaA 0%.
Keywords: Bacterial vaginosis, virulence factor sgenes PCR, BV.